Characterization of chemical profile and quantification of major representative components of Wendan decoction, a classical traditional Chinese medicine formula. Issue 5 (25th January 2021) - Wang, Qi; Zou, Zhenyu; Zhang, Yezi; Lin, Pei; Lan, Taohua; Qin, Zifei; Xu, Danping; Wu, Huanlin; Yao, Zhihong
Abstract: Wendan decoction, a classical traditional Chinese medicine formula consisting of six herbal medicines, has been widely used in clinical treatments for thousands of years due to the expectorant effects. However, the chemical basis of Wendan decoction remains unclear, which hinders the elucidation of the scientific connotation and mechanism of its effective components. In this study, an ultra‐high performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry method was first developed for characterization of its chemical profile, and a total of 142 chemical components including flavonoids, triterpenoids, alkaloids, coumarins, pungent phytochemicals, and other types were detected, among which 41 components were definitively identified with authentic standards. Furthermore, 14 major representative components were simultaneously quantified by high‐performance liquid chromatography with ultraviolet detector, indicating that the content levels of flavonoids were the most abundant in Wendan decoction. In summary, this study established sensitive and practical methods to systematically characterize chemical profile for the first time and simultaneous quantify representative components of Wendan decoction. These findings above would provide a solid chemical basis for disclosure of potential effective components by further in vivo disposal study, and promote therapeutic mechanism researches of Wendan decoction.